2019
DOI: 10.1002/jper.18-0585
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease may induce liver fibrosis in an experimental study on Wistar rats

Abstract: Background The aim was to assess the effects of periodontal disease in promoting liver fibrosis in a rat model of ligature‐induced periodontitis. Methods Twenty‐four Wistar rats were divided into four groups: control (CTRL), experimental periodontitis group at day 7 (PER7), at day 14 (PER14), at day 21 (PER21). Experimental periodontitis was induced by the placement of a silk ligature around mandibular incisors. The following parameters were assessed: gingival index, tooth mobility; liver status, and portal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…One animal study showed that periodontitis induced by virulent periodontal factors determined oxidative damage of the liver in rats (Tomofuji et al, 2007). A previous study confirmed that experimental periodontitis induced the increasing level of the oxidative stress parameters and liver fibrosis in rats (Mester et al, 2019). In this study, a significant relationship was observed between CAL and liver fibrosis, while no association was found in PD.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…One animal study showed that periodontitis induced by virulent periodontal factors determined oxidative damage of the liver in rats (Tomofuji et al, 2007). A previous study confirmed that experimental periodontitis induced the increasing level of the oxidative stress parameters and liver fibrosis in rats (Mester et al, 2019). In this study, a significant relationship was observed between CAL and liver fibrosis, while no association was found in PD.…”
Section: Discussionsupporting
confidence: 73%
“…These contributors act in a coordinated and cooperative manner to promote hepatic inflammation and fibrosis (Tilg & Moschen, 2010). Periodontitis could promote hepatic injury by increasing systemic inflammation and oxidative stress (Alazawi et al, 2017; Mester et al, 2019). One animal study showed that periodontitis induced by virulent periodontal factors determined oxidative damage of the liver in rats (Tomofuji et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Micro-CT images of the right halves were taken with Skyscan (Bruker MicroCT, Kontich, Belgium) after macroscopic examination. Three-dimensional reconstructions were made and analyzed by NRecon 1.6.3 (Brucker MicroCT) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tooth mobility (TM) was elevated according to the following scale: 0 = physiological mobility; 1 = slight mobility in buccolingual direction; 2 = moderate mobility in buccolingual and mesiodistal directions; and 3 = severe mobility in buccolingual, mesiodistal, and vertical directions (Mester et al., 2019).…”
Section: Methodsmentioning
confidence: 99%